(untitled) (Mongolian Journal of Agricultural Sciences, 2018)
Papaver nudicaule L has a long history as a being useful for the treatment of many diseases in Asian and European countries. Aim of this study was to cultivate callus and cell suspension culture in vitro using plant phytohormones. The proliferative capacity was tested on shoot cultivated on Murashige-Skoog (MS) basal medium testing auxins: -Naphthaleneacetic acid (NAA) in combination with cytokinine: 6-Benzylaminopurine. We determined production of alkaloids by four-week old callus and cell suspension biomass of Papaver nudicaule using thin layer chromatography comparing standard sanguianarine. This result displayed us the easier approach to isolate pure one alkaloid from the biomass that those whole- plant. Нүцгэн намуу ургамлын in vitro биомасс дахь алкалоид Хураангуй: Нүцгэн намуу (Papaver nudicaule) нь эмийн болон чимэглэлийн ач холбогдолтой ургамал юм. Уг ургамлын үрээс каллусын болон эсийн суспензийн биомассыг гарган авахдаа нафтален цууны хүчил болон бензил аденин өсөлтийн бодисын хослол бүхий тэжээлт орчинд өсгөвөрлөн өсөлтийн параметрүүдийг тогтоолоо. Ургамлын in vitro биомасст нимгэн үеийн хроматографийн аргаар сангвинарин алкалоидыг стандарт бодистой харьцуулан тодорхойлов. Сангвинарин нь ургамлын эд эрхтэний төрөлжилтөөс үл хамааран үүсдэг биологийн өндөр идэвхтэй хоёрдогч нийлэгжилтийн бүтээгдэхүүн юм. Түлхүүр үг: өсөлтийн гормоны хослол, каллусын эд, суспензийн нягт, нимгэн үеийн хроматографи